2016
DOI: 10.5937/savteh1602064s
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the variation of texturing process parameters on structural characteristics of polyamide textured yarns in the false twist

Abstract: The variation of texturing process parameters within the limits of the industrial texturing machine brings about substantial structural changes of yarn characteristics. To obtain required characteristics of textured PA6.6 yarns for specific purposes, it is necessary to adjust the optimum process parameters. For that reason, in addition to modification of the quality of textured polyamide yarns, the aim of this work is to define the limit values of the texturing process. In this work, the influence of technical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…This is important for the later dyeing of the yarn, as an increased content of end groups is important for yarn dyeing quality and levelling. All in all, the influence of temperature is higher than that of the texturing speed and the D/Y ratio, as expected [82].…”
Section: Polyamidesupporting
confidence: 79%
“…This is important for the later dyeing of the yarn, as an increased content of end groups is important for yarn dyeing quality and levelling. All in all, the influence of temperature is higher than that of the texturing speed and the D/Y ratio, as expected [82].…”
Section: Polyamidesupporting
confidence: 79%
“…(Savić et al ., 2016), focusing on polyamide 6.6 yarn, delved into the effect of texturing process parameters on the characteristics of the texturized yarn. Through their research, they identified the optimal values for each parameter, aiming to optimize the quality attributes of the texturized yarn.…”
Section: Literature Reviewmentioning
confidence: 99%
“…All in all the influence of temperature is higher than the texturing speed and the D/Y ratio, as expected. [83]…”
Section: Polyamidementioning
confidence: 99%